Experimental investigation of PCM based round pin-fin heat sinks for thermal management of electronics: effect of pin-fin diameter - Arshad, Adeel; Ali, Hafiz Muhammad; Khushnood, Shahab; Jabbal, Mark (Elsevier, 2017)
This experimental study presents the parametric analysis for the round pin-finned heat sinks subjected to steady heat densities for effective and reliable cooling of mobile electronic devices. Phase change material (PCM) namely paraffin wax is adopted as energy storage material and aluminum made round pin-fins are selected as thermal conductivity enhancers (TCEs). A constant volume fraction of 9% of round pin-fins is selected with pin diameter of 2